STRATEGI KERUANGAN UNTUK MENINGKATKAN AKSES MASYARAKAT KELURAHAN TAMBAKJATI KABUPATEN SUBANG TERHADAP AIR BERSIH - Sri Maryati (Purifikasi, 2011)
Tambakjati Subdistrict is located in Subang District and is one area that has a problem in the provision of drinking water. There are a number of water resources in Tambakjati Village, but the local people do not have good access to reach. This limitation is due to the high costs for investment and operations, while the economic capacity of local communities is very low. Therefore, it needs the intervention of local governments to provide clean water, which is accessible to the entire community. However, provision of clean water can still be pursued for cost recovery. Therefore, it needs a number of strategies to adjust the cost for supplying drinking water with a willingness to pay from the community. This study will analyze a number of spatial strategies in the provision of clean water in Tambakjati Village to adjust to the cost of supplying drinking water to the willingness to pay from the community.